TABOO AND EUPHEMISM - Islamova Ezoza Yorkin kizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article provides information on linguo-cultural studies. The features of expression of traditional words, the expression of taboos and euphemisms in traditional lexemes, the concepts of taboo and euphemism, their importance in language use and their impact on society are discussed.